(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
The article explores the issue of the plurality of cultural traditions in US literature and art, focusing on the interplay between Western and Eastern influences, particularly in the context of American multiculturalism. The work of Pearl Buck is examined as a precursor to contemporary discussions on multiculturalism, focusing on themes of national, ethnic, and cultural identity, as well as the complexities of "us" versus "them" dynamics. Buck’s exploration of hybridity and her quest for harmony between East and West are noted as pivotal in bridging cultural divides and fostering mutual understanding.